Decoding school safety: exploring the effectiveness of safety signs based on the perceptions of the primary school children in Zhengzhou, China - Wang, Tong xu; Abdul Shukor, Shureen Faris; Kozlowski, Marek; Wan Mohamed, Wan Srihani; Zhang, Ting (Green Publication, 2024)
In 2010, unintentional injuries represented 12% of the 5.1 million injury-related fatalities worldwide among individuals aged 1 to 19 years. Although this significant health issue exists, childhood injuries still remain relatively neglected in global health efforts nowadays. This study employed a non-probability sampling method to empirically investigate the presence and effectiveness of school safety signs among children in a primary school in Zhengzhou, China. The aim is to provide new insights into safety research within the context of school health, contributing both theoretically and practically. It uses a quantitative method, including the distribution of questionnaires, the use of KMO sample measurement to check the validity of the questionnaire, the construction of thematic models and research hypotheses, and one-way ANOVA to test the hypotheses. The preliminary findings have stated that the effectiveness of safety signs is influenced by both the characteristics of their visual elements and the personal traits of the information receivers. The proposed design recommendations for school safety signs will benefit school children and safety sign designers.